Preparation method of barium sulfate coated calcium carbonate core-shell structure
By converting sulfuric acid on the CaCO3@BaCO3 core-shell structure, the CaCO3@BaSO4 core-shell structure is solved, and the problems of uneven surface coating and high production cost are significantly improved. The acid resistance and stability of calcium carbonate are greatly improved. , suitable for industrial applications.
Patent Information
- Application Number
- CN202411622526.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-14
- Publication Date
- 2025-01-07
AI Technical Summary
The existing barium sulfate-coated calcium carbonate technology has problems such as poor affinity, uneven coating and high production costs, which limits the application range and acid resistance of calcium carbonate.
Using the indirect preparation method, sulfuric acid is first added on the basis of the CaCO3@BaCO3 core-shell structure, and the CaCO3@BaSO4 core-shell structure is generated through chemical conversion reaction, so that the surface of calcium carbonate is completely uniformly coated with barium sulfate, with simple process and product shape Regular appearance.
It realizes uniform surface coating of calcium carbonate, significantly improves the acid resistance and stability of the material, reduces production costs, and is suitable for industrial applications.
Smart Images

Figure CN119263333A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of calcium carbonate preparation, and in particular to a method for preparing a barium sulfate-coated calcium carbonate core-shell structure. Technical Background
[0002] Barium sulfate is an inorganic compound that is only soluble in hot concentrated sulfuric acid. It has stable physical and chemical properties and excellent acid and alkali resistance. It is the only non-toxic barium salt. It exists in the form of barite in nature and has good weather resistance and corrosion resistance. These many advantages make barium sulfate widely used in many fields. For example, in the papermaking industry, barium sulfate can be used as a filler and bleaching pulping agent, which can significantly improve the whiteness and glossiness of paper, while controlling the viscosity of the slurry to make the quality of paper more stable and consistent; in the rubber industry, barium sulfate, as a filler, can enhance the hardness and strength of rubber, improve wear resistance and aging resistance; used in coatings, barium sulfate can make the coating more uniform and smooth, and improve the hiding power and durability of the coating.
[0003] Calcium carbonate, an inorganic compound composed of three elements, C, O, and Ca, is the main component of limestone, calcite, marble, dolomite, chalk, coral, and shells, and is widely present in nature. As an important mineral resource, calcium carbonate has the advantages of wide sources, low prices, and unique physical and chemical properties. It is often used as a filler in rubber, plastics, papermaking, coatings and other industries, and plays an important role in the development of modern industry. With the rapid development of industry, the market demand for calcium carbonate products is increasing, and the quality requirements for calcium carbonate products are also getting higher and higher. Calcium carbonate has strong alkalinity due to the presence of hydroxyl groups on its surface. It is easy to decompose under acidic conditions and can only be used in neutral or alkaline environments. This defect seriously limits the application of calcium carbonate.
[0004] Surface modification is one of the key technologies to optimize the performance of inorganic powder materials, and plays a vital role in improving the application performance and value of inorganic powder materials. Therefore, in order to solve the poor acid resistance of calcium carbonate and expand the application range of calcium carbonate, it is of great significance to modify the dissolution inhibition of calcium carbonate filler, and coating a layer of barium sulfate on the surface of calcium carbonate is an effective measure.
[0005] Gao Hongxia et al. used the in-situ deposition method to coat and modify precipitated calcium carbonate (PCC) with barium sulfate generated by the reaction of barium chloride and sodium sulfate at 25°C and 90°C, respectively. The surface of the modified PCC was coated with barium sulfate, and its solubility in distilled water with a pH value of 6.50 was reduced. The modified PCC was applied to acid papermaking, which can improve the pulping degree of paper stock, and the whiteness, opacity and light scattering coefficient of the paper were all improved (Gao Hongxia, Xu Yang, Fu Maogang, Pan Rao; Research on surface coating modification and application of precipitated calcium carbonate based on in-situ deposition of barium sulfate [J]. "China Papermaking" 2016 Vol. 35 No. 9).
[0006] Wang Sha used the precipitation method to deposit a large amount of barium sulfate generated by the reaction of aluminum sulfate and barium chloride on the surface of precipitated calcium carbonate particles, and then applied the modified precipitated calcium carbonate filler to paper manufacturing. The addition of precipitated calcium carbonate filler can replace pulp fiber to a certain extent, effectively control the amount of raw materials, and have a very ideal improvement effect on the optical properties of paper products such as whiteness and opacity (Wang Sha; Research on the modification of precipitated calcium carbonate filler and its application in papermaking [J]. East China Paper Industry, 1674-6937 (2020) 03-0001-03).
[0007] Both of the above technologies deposit barium sulfate onto the surface of calcium carbonate by precipitation to achieve the effect of modifying calcium carbonate. However, the affinity between calcium carbonate and barium sulfate is very poor, and barium sulfate is only adsorbed on the surface of calcium carbonate in the form of particles, making it difficult to form a coating layer.
[0008] Patent CN 114408957 A discloses a method for coating calcium carbonate with barium sulfate. In the preparation process of calcium carbonate, CaCO is first prepared by coprecipitation. 3 @BaCO 3 The core-shell structure is then introduced into the sulfur dioxide gas, and the CaCO 3 @BaCO 3 Converted to CaCO 3 @BaSO 4 This method can make barium sulfate evenly coated on the surface of calcium carbonate to form a barium sulfate coating layer. However, this method is to add barium ions at the end of the preparation of calcium carbonate, and by controlling the remaining amount of calcium ions in the solution, the BaCO 3 and CaCO 3 coprecipitate onto the surface of the initially generated calcium carbonate to obtain CaCO 3 @BaCO 3 The core-shell structure and the addition of barium ions are difficult to control, which may lead to the formation of different crystalline calcium carbonates. 3 @BaSO 4The core-shell structure product has a general morphology and poor dispersibility; in addition, the preparation process of sulfur dioxide gas is relatively complicated and the production cost is high, which is not conducive to industrial production.
[0009] In summary, it can be found that the currently disclosed technologies for coating calcium carbonate with barium sulfate are relatively few and all have certain defects. Therefore, it is necessary to study and develop a suitable process technology for preparing a core-shell structure composite powder of calcium carbonate coated with barium sulfate to achieve CaCO 3 and BaSO 4 The effective combination of can improve the acid resistance of calcium carbonate, which is of great significance to the development of the calcium carbonate industry. Summary of the invention
[0010] In view of the above problems, the present invention provides a method for preparing a core-shell structure of calcium carbonate coated with barium sulfate, which is an indirect preparation method. First, Ba 2+ In Ca 2+ In the presence of CO 3 2- Reaction, the generated BaCO 3 With CaCO 3 coprecipitate onto the surface of the core calcium carbonate to form CaCO 3 @BaCO 3 Core-shell structure, and then sulfuric acid is added to obtain CaCO through chemical conversion reaction. 3 @BaSO 4 Core-shell structure. This method is simple in process and can obtain a core-shell structure product in which the surface of calcium carbonate is completely and evenly coated with barium sulfate. The coating effect is good, and the product has a regular morphology and good acid resistance.
[0011] To achieve the above object, the present invention adopts the following technical solution:
[0012] A method for preparing a barium sulfate-coated calcium carbonate core-shell structure comprises the following steps:
[0013] (1) preparing calcium chloride and sodium carbonate solutions respectively, and then quickly mixing the two to prepare calcium carbonate, thereby obtaining a calcium carbonate suspension;
[0014] (2) adding carbonate to the calcium carbonate suspension obtained in step (1), stirring to dissolve and fully mixing with calcium carbonate, and then dropping a mixed solution containing a calcium source and a barium source to react to obtain CaCO 3 @BaCO 3 Serum;
[0015] (3) To the CaCO obtained in step (2) 3 @BaCO 3 Sulfuric acid is added dropwise to the slurry to obtain CaCO 3 @BaSO4 Serum;
[0016] (4) The CaCO obtained in step (3) 3 @BaSO 4 The slurry is filtered, washed and dried to obtain CaCO 3 @BaSO 4 Composite powder, namely BaSO 4 Coated CaCO 3 core-shell structure.
[0017] Preferably, in step (1), the concentrations of calcium chloride and sodium carbonate are both 0.1-1.0 mol / L.
[0018] Preferably, in step (1), the particle size of calcium carbonate in the calcium carbonate suspension is 2-5 μm.
[0019] Preferably, in step (2), the carbonate comprises one or more of sodium carbonate, potassium carbonate, ammonium carbonate and ammonium bicarbonate, and the amount added is calculated based on the amount that can just react completely with the calcium source and the barium source.
[0020] Preferably, in step (2), the calcium source comprises one or more of calcium chloride, calcium nitrate and calcium hydroxide, and the amount added is calculated as 0.4-1 times the amount of the barium source.
[0021] Preferably, in step (2), the barium source includes one or more of barium chloride, barium nitrate, and barium hydroxide, and the amount thereof added is sufficient to generate BaCO 3 The weight is calculated as 2%-10% of the weight of calcium carbonate.
[0022] Preferably, in step (2), the concentration of the mixed solution of the calcium source and the barium source is 0.1-1.0 mol / L, and the dropping rate is 5-20 mL / min.
[0023] Preferably, the reaction time in step (2) is 1-3 h, and the reaction time in step (3) is 1-2 h.
[0024] Preferably, in step (3), the concentration of sulfuric acid is 0.1-1.0 mol / L, and the dropping rate is 2-10 mL / min.
[0025] Preferably, in step (4), the drying method is: drying in a forced air drying oven at a temperature of 105-150° C. for 12-24 hours.
[0026] Compared with the prior art, the present invention has the following technical advantages:
[0027] The preparation method pioneered by this invention has demonstrated unprecedented technological innovation and significant progress in the fields of chemical engineering and materials science. Through a carefully designed coprecipitation strategy, we have cleverly achieved BaCO 3 With CaCO 3 The close integration at the molecular scale requires not only a high degree of chemical precision, but also depends on the fine control of reaction conditions. This unique co-precipitation technology makes the generated BaCO 3 It can be deposited evenly and densely on the surface of the core calcium carbonate, forming a CaCO 3 @BaCO 3 Core-shell structure. This innovation has greatly overcome the problems of uneven coating and multiple interface defects that are difficult to avoid in traditional coating technology, laying a solid foundation for subsequent chemical transformation.
[0028] Furthermore, the present invention utilizes sulfuric acid and CaCO 3 @BaCO 3 BaCO in core-shell structure 3 An efficient chemical reaction occurred, successfully converting BaCO 3 Converted to BaSO 4 , thus obtaining CaCO with excellent performance 3 @BaSO 4 Core-shell structure product. This conversion process not only retains the integrity of the original core-shell structure, but also greatly improves the acid resistance of the material through the uniform coating of barium sulfate. As a highly stable inorganic salt, barium sulfate has a dense and uniform coating layer that effectively blocks the external acidic medium from corroding the internal calcium carbonate core, making the core-shell structure material show excellent stability and durability in an acidic environment.
[0029] In addition, the preparation method of the present invention also has significant process advantages. The steps are concise and clear, the operation is simple and easy, and no complex and expensive equipment or special reaction conditions are required, which greatly reduces the production cost and improves the production efficiency. At the same time, the method has a high yield and repeatability, and can stably prepare CaCO with regular morphology and good coating effect. 3 @BaSO 4 Core-shell structure products, which are of great significance for promoting the industrial application of related materials.
[0030] In summary, the preparation method of indirect barium sulfate-coated calcium carbonate proposed in the present invention has not only achieved significant technical progress, opened up a new path for the preparation of calcium carbonate core-shell structure, but also demonstrated great potential and value in terms of material properties, production costs and industrial applications. This innovative achievement will undoubtedly arouse widespread attention and in-depth research in many fields such as chemical engineering, materials science, and environmental protection, and inject new vitality into the scientific and technological progress and industrial development in related fields. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 The CaCO prepared in Example 1 3 @BaSO 4 SEM images of the core-shell structure;
[0032] Figure 2 The CaCO prepared in Example 2 3 @BaSO 4 SEM images of the core-shell structure;
[0033] Figure 3 The CaCO prepared in Example 3 3 @BaSO 4 SEM images of the core-shell structure;
[0034] Figure 4 The CaCO prepared in Example 4 3 @BaSO 4 SEM images of the core-shell structure;
[0035] Figure 5 The SEM image of the blank calcium carbonate prepared in Comparative Example 1;
[0036] Figure 6 The CaCO prepared in Comparative Example 2 3 @BaCO 3 SEM images of the core-shell structure;
[0037] Figure 7 The CaCO prepared in Comparative Example 3 3 @BaSO 4 SEM images of the core-shell structure;
[0038] Figure 8 is the XRD pattern before and after calcium carbonate coating;
[0039] Fig. 9 This is the acid resistance test result before and after calcium carbonate coating. DETAILED DESCRIPTION
[0040] In order to better present the present invention, it is illustrated through specific implementation cases, which belong to the protection scope of the present invention but do not limit the protection scope of the present invention.
[0041] In an embodiment of the present invention, a method for preparing a barium sulfate-coated calcium carbonate core-shell structure comprises the following steps:
[0042] (1) preparing calcium chloride and sodium carbonate solutions respectively, and then quickly mixing the two to prepare calcium carbonate, thereby obtaining a calcium carbonate suspension;
[0043] (2) Add carbonate to the calcium carbonate suspension obtained in step (1), stir to dissolve it and mix it with calcium carbonate, then dropwise add a mixed solution containing a calcium source and a barium source, and react for 1-3 hours to obtain CaCO 3 @BaCO 3 Serum;
[0044] (3) To the CaCO obtained in step (2) 3 @BaCO 3 Sulfuric acid was added dropwise to the slurry and reacted for 1-2h to obtain CaCO 3 @BaSO 4 Serum;
[0045] (4) The CaCO obtained in step (3) 3 @BaSO 4 The slurry is filtered, washed and dried to obtain CaCO 3 @BaSO 4 Composite powder, namely BaSO 4 Coated CaCO 3 core-shell structure.
[0046] In step (1), the concentrations of calcium chloride and sodium carbonate are both 0.1-1.0 mol / L.
[0047] In step (1), the particle size of calcium carbonate in the calcium carbonate suspension is 2 μm-5 μm.
[0048] In step (2), the carbonate includes one or more of sodium carbonate, potassium carbonate, ammonium carbonate, and ammonium bicarbonate, and the amount added is calculated based on the amount that can completely react with the calcium salt and the barium salt.
[0049] In step (2), the calcium source includes one or more of calcium chloride, calcium nitrate and calcium hydroxide, and the added amount thereof is calculated as 0.4-2 times the amount of the barium source.
[0050] In step (2), the barium source includes one or more of barium chloride, barium nitrate, and barium hydroxide, and the amount of the barium source added is sufficient to generate BaCO 3 The weight is calculated as 2%-10% of the weight of calcium carbonate.
[0051] In step (2), the concentration of the mixed solution of the calcium source and the barium source is 0.1-1.0 mol / L, and the dropping rate is 5-20 mL / min.
[0052] In step (3), the concentration of sulfuric acid is 0.1-1.0 mol / L, and the dropping rate is 2-10 mL / min.
[0053] In step (4), the drying method is: drying in a forced air drying oven at a temperature of 120-150° C. for 12-24 hours.
[0054] Technical principle of the present invention:
[0055] When deeply discussing the preparation method of the barium sulfate-coated calcium carbonate core-shell structure of the present invention, we not only need to describe its operating steps in detail, but also need to deeply analyze the specific role of the raw materials in each step, the synergistic mechanism between the raw materials, and the key influence of process parameter optimization on the performance improvement of the final product.
[0056] 1. Specific role and synergistic mechanism of raw materials
[0057] (1) Rapid mixing of calcium chloride and sodium carbonate solution
[0058] This step is the basis for forming the calcium carbonate core. Calcium chloride, as a calcium source, reacts quickly and efficiently with sodium carbonate to produce calcium carbonate particles with a particle size uniformly distributed in the range of 2μm to 5μm. The selection of this particle size range is intended to provide a stable support structure for the subsequent coating layer, while ensuring that the coating layer can be evenly covered without obvious agglomeration or cracks. As a source of carbonate ions, sodium carbonate is controlled in concentration (0.1-1.0 mol / L) to ensure a moderate reaction rate, neither too fast to cause excessive particle refinement, nor too slow to affect production efficiency.
[0059] (2) Addition of carbonate and dropwise addition of mixed solution of calcium source and barium source
[0060] Adding an appropriate amount of carbonate (such as sodium carbonate, potassium carbonate, etc.) to the calcium carbonate suspension not only adjusts the pH value of the system, but also provides a precursor for the subsequent coating layer, BaCO 3 The mixed solution of calcium source (such as calcium chloride, calcium nitrate) and barium source (such as barium chloride, barium nitrate) gradually reacts with carbonate ions in the system at a controlled drop rate (5-20mL / min) to form BaCO 3 A thin layer initially covered with CaCO 3 In this step, the molar ratio of calcium source to barium source is carefully controlled (calcium source is 0.4-2 times of barium source), ensuring that BaCO 3 The appropriate amount of BaCO is generated, which neither affects the performance of the core material too much nor causes incomplete coating.3 The amount of production (accounting for CaCO 3 The weight of the coating (2%-10%) is precisely calculated to optimize the thickness of the coating and enhance the stability and functionality of the composite material.
[0061] (3) Addition of sulfuric acid
[0062] In the formation of CaCO 3 @BaCO 3 After slurry, the addition of sulfuric acid is a key step. 3 Reaction to form water-insoluble BaSO 4 , thus converting the original BaCO 3 Layer conversion to BaSO 4 Coating layer. The selection of sulfuric acid concentration (0.1-1.0 mol / L) and dripping rate (2-10 mL / min) is directly related to the density and uniformity of the coating layer. Appropriate concentration and dripping rate can ensure a smooth reaction and avoid uneven coating caused by excessive local concentration or structural defects caused by too fast a reaction.
[0063] 2. Necessity and importance of process parameter optimization
[0064] (1) Precise control of raw material dosage: The amount of raw materials used in each step is carefully calculated to ensure that the reaction proceeds as expected. Excessive or insufficient raw materials will affect the performance of the product, such as the thickness and density of the coating layer and the stability of the core material.
[0065] (2) Optimization of process parameters: The adjustment of parameters such as droplet acceleration rate, reaction time, and drying conditions is directly related to the microstructure and macroscopic performance of the product. By continuously optimizing these parameters, the uniformity, density, and stability of the product can be significantly improved, thereby giving it better physical and chemical properties.
[0066] 3. Unexpected technical effects
[0067] Through the above-mentioned careful raw material selection and process optimization, the prepared barium sulfate-coated calcium carbonate core-shell structure exhibited a series of unexpected technical effects. First, BaSO 4 As the outer coating material, it greatly improves the acid resistance, thermal stability and mechanical strength of the composite material, allowing it to be used in a wider range of fields. Secondly, the unique design of the core-shell structure enables the composite material to exhibit better performance when used as a filler, catalyst carrier or biomedical material, such as better dispersibility, higher loading capacity and lower biological toxicity. The realization of these technical effects not only broadens the application scope of calcium carbonate-based composite materials, but also provides new ideas and methods for technological progress in related fields.
[0068] In order to make the disclosure of the present invention more complete, it is described below through more specific embodiments.
[0069] Example 1
[0070] A method for preparing a barium sulfate-coated calcium carbonate core-shell structure comprises the following steps:
[0071] (1) preparing a 0.1 mol / L calcium chloride solution and a 0.1 mol / L sodium carbonate solution, and rapidly mixing the two under rapid stirring to obtain a calcium carbonate suspension;
[0072] (2) adding sodium carbonate to the calcium carbonate suspension obtained in step (1) in an amount sufficient to react completely with calcium chloride and barium chloride, stirring to dissolve and fully mixing with calcium carbonate, and then dripping a mixed solution of calcium chloride and barium chloride at a concentration of 1 mol / L and a molar ratio of 1:1 at a rate of 2 mL / min, wherein the amount of barium chloride added is sufficient to generate BaCO 3 The weight is calculated as 5% of the weight of calcium carbonate, and the reaction is carried out for 2h to obtain CaCO 3 @BaCO 3 Serum;
[0073] (3) To the CaCO obtained in step (2) 3 @BaCO 3 The concentration of sulfuric acid added to the slurry was 0.5 mol / L, and the rate of addition was 2 mL / min. The amount added was just enough to react with BaCO 3 Complete reaction, 1h reaction to obtain CaCO 3 @BaSO 4 Serum;
[0074] (4) The CaCO obtained in step (3) 3 @BaSO 4 The slurry was filtered, washed, and dried in a forced air drying oven at 120°C for 20 h to obtain CaCO 3 @BaSO 4 Composite powder, namely BaSO 4 Coated CaCO 3 core-shell structure.
[0075] Example 2
[0076] A method for preparing a barium sulfate-coated calcium carbonate core-shell structure comprises the following steps:
[0077] (1) preparing a 0.5 mol / L calcium chloride solution and a 0.5 mol / L sodium carbonate solution, and rapidly mixing the two under rapid stirring to obtain a calcium carbonate suspension;
[0078] (2) adding ammonium carbonate to the calcium carbonate suspension obtained in step (1) in an amount sufficient to react completely with calcium nitrate and barium nitrate, stirring to dissolve and fully mixing with calcium carbonate, and then dripping a mixed solution of calcium nitrate and barium nitrate in a molar ratio of 2:1 with a concentration of 0.5 mol / L at a rate of 5 mL / min, wherein the amount of barium nitrate added is sufficient to generate BaCO 3 The weight is calculated as 2% of the weight of calcium carbonate, and the reaction is carried out for 1h to obtain CaCO 3 @BaCO 3 Serum;
[0079] (3) To the CaCO obtained in step (2) 3 @BaCO 3 The concentration of sulfuric acid added to the slurry was 0.1 mol / L, and the rate of addition was 10 mL / min. The amount added was just enough to react with BaCO 3 Complete reaction, 1h reaction to obtain CaCO 3 @BaSO 4 Serum;
[0080] (4) The CaCO obtained in step (3) 3 @BaSO 4 The slurry was filtered, washed, and dried in a forced air drying oven at 150°C for 10 h to obtain CaCO 3 @BaSO 4 Composite powder, namely BaSO 4 Coated CaCO 3 core-shell structure.
[0081] Example 3
[0082] A method for preparing a barium sulfate-coated calcium carbonate core-shell structure comprises the following steps:
[0083] (1) preparing a 0.8 mol / L calcium chloride solution and a 0.8 mol / L sodium carbonate solution, and rapidly mixing the two under rapid stirring to obtain a calcium carbonate suspension;
[0084] (2) adding potassium carbonate to the calcium carbonate suspension obtained in step (1) in an amount sufficient to react completely with calcium hydroxide and barium hydroxide, stirring to dissolve and fully mixing with calcium carbonate, and then dripping a mixed solution of calcium hydroxide and barium hydroxide at a concentration of 0.7 mol / L and a molar ratio of 2:5 at a rate of 10 mL / min, wherein the amount of barium hydroxide added is sufficient to generate BaCO 3 The weight is calculated as 8% of the weight of calcium carbonate, and the reaction is carried out for 2h to obtain CaCO 3 @BaCO 3 Serum;
[0085] (3) To the CaCO obtained in step (2) 3 @BaCO 3 The concentration of sulfuric acid added to the slurry was 1 mol / L, and the rate of addition was 1 mL / min. The amount added was just enough to absorb the BaCO 3 Complete reaction, reaction time 2h to obtain CaCO 3 @BaSO 4 Serum;
[0086] (4) The CaCO obtained in step (3) 3 @BaSO 4 The slurry was filtered, washed, and dried in a forced air drying oven at 130°C for 16 h to obtain CaCO 3 @BaSO 4 Composite powder, namely BaSO 4 Coated CaCO 3 core-shell structure.
[0087] Example 4
[0088] A method for preparing a barium sulfate-coated calcium carbonate core-shell structure comprises the following steps:
[0089] (1) preparing a 1 mol / L calcium chloride solution and a 1 mol / L sodium carbonate solution, and rapidly mixing the two under rapid stirring to obtain a calcium carbonate suspension;
[0090] (2) adding ammonium bicarbonate to the calcium carbonate suspension obtained in step (1) in an amount sufficient to react completely with calcium nitrate and barium hydroxide, stirring to dissolve the ammonium bicarbonate and mixing the ammonium bicarbonate with the calcium carbonate, and then dripping a mixed solution of calcium nitrate and barium hydroxide at a concentration of 0.1 mol / L and a molar ratio of 1:2 at a rate of 10 mL / min, wherein the amount of barium chloride added is sufficient to generate BaCO 3 The weight of calcium carbonate is calculated as 10% of the weight of calcium carbonate. After reacting for 3 hours, CaCO 3 @BaCO 3 Serum;
[0091] (3) To the CaCO obtained in step (2) 3 @BaCO 3 The concentration of sulfuric acid added to the slurry was 0.3 mol / L, and the rate of addition was 8 mL / min. The amount added was just enough to react with BaCO 3 Complete reaction, reaction time 2h to obtain CaCO 3 @BaSO 4 Serum;
[0092] (4) The CaCO obtained in step (3) 3 @BaSO 4The slurry was filtered, washed, and dried in a forced air drying oven at 105°C for 24 h to obtain CaCO 3 @BaSO 4 Composite powder, namely BaSO 4 Coated CaCO 3 core-shell structure.
[0093] Comparative Example 1
[0094] A method for preparing calcium carbonate powder comprises the following steps:
[0095] (1) preparing a 0.5 mol / L calcium chloride solution and a 0.5 mol / L sodium carbonate solution, and rapidly mixing the two under rapid stirring to obtain a calcium carbonate suspension;
[0096] (2) The calcium carbonate suspension obtained in step (1) is filtered, washed, and dried in a forced air drying oven at 130° C. for 16 h to obtain blank calcium carbonate powder.
[0097] Comparative Example 2
[0098] A CaCO 3 @BaCO 3 The method for preparing a core-shell structure comprises the following steps:
[0099] (1) preparing a 0.5 mol / L calcium chloride solution and a 0.5 mol / L sodium carbonate solution, and rapidly mixing the two under rapid stirring to obtain a calcium carbonate suspension;
[0100] (2) adding sodium carbonate to the calcium carbonate suspension obtained in step (1) in an amount sufficient to react completely with calcium chloride and barium chloride, stirring to dissolve and fully mixing with calcium carbonate, and then dripping a mixed solution of calcium chloride and barium chloride at a concentration of 0.5 mol / L and a molar ratio of 1:2 at a rate of 5 mL / min, wherein the amount of barium chloride added is sufficient to generate BaCO 3 The weight is calculated as 5% of the weight of calcium carbonate, and the reaction is carried out for 2h to obtain CaCO 3 @BaCO 3 Serum;
[0101] (3) The CaCO obtained in step (4) 3 @BaCO 3 The slurry was filtered, washed, and dried in a forced air drying oven at 130°C for 16 h to obtain CaCO 3 @BaCO 3 Core-shell structure.
[0102] Comparative Example 3
[0103] A CaCO 3 @BaSO4 The method for preparing the composite powder comprises the following steps:
[0104] (1) preparing a 0.1 mol / L calcium chloride solution and a 0.1 mol / L sodium carbonate solution, and rapidly mixing the two under rapid stirring to obtain a calcium carbonate suspension;
[0105] (2) adding barium chloride to the calcium carbonate suspension obtained in step (1) in an amount sufficient to generate BaSO 4 The weight of barium chloride is calculated as 5% of the weight of calcium carbonate. After stirring to dissolve and fully mix with calcium carbonate, a sulfuric acid solution with a concentration of 0.1 mol / L is added dropwise at 2 mL / min. The amount added is just enough to react completely with barium chloride. The reaction is continued for 2 h to obtain CaCO 3 @BaSO 4 Serum;
[0106] (3) The CaCO obtained in step (2) 3 @BaSO 4 The slurry was filtered, washed, and dried in a forced air drying oven at 120°C for 20 h to obtain CaCO 3 @BaSO 4 Composite powder.
[0107] Product performance test:
[0108] (1) The products prepared in Examples 1-4 and Comparative Examples 1-3 were tested by scanning electron microscopy. The test results are as follows: Figure 1-7 shown. Figure 5 This is the SEM image of blank calcium carbonate in comparative example 1. When not coated, the surface of calcium carbonate is smooth. After coated with barium carbonate, under the scanning electron microscope, the surface of calcium carbonate still maintains a smooth shape, but becomes whiter. When CaCO 3 @BaCO 3 Reacts with sulfuric acid to form CaCO 3 @BaSO 4 After that, the surface of calcium carbonate becomes rough. Figure 8 The XRD pattern proves that the surface of calcium carbonate is coated with a barium sulfate coating.
[0109] from Figure 1-4 It can be seen that the coated calcium carbonate powders prepared in Examples 1-4 of the present invention have regular morphology, and the surface of the calcium carbonate is evenly and completely wrapped by the barium sulfate coating layer composed of barium sulfate particles. As the coating amount increases, the generated barium sulfate particles gradually increase in size and the coating layer thickens. When the coating amount is 5%, the barium sulfate coating layer formed on the surface of the calcium carbonate is the best ( Figure 1 ).Depend on Figure 7 The SEM image of Comparative Example 3 shows that Ba 2+ Necessary in Ca 2+In the presence of CO3 2- Reaction, with CaCO 3 Co-precipitation onto the surface of the core calcium carbonate can ultimately form CaCO 3 @BaSO 4 Core-shell structure.
[0110] (2) CaCO 3 @BaSO 4 Acid resistance test of core-shell structure
[0111] The specific operation process of the acid resistance test is as follows: weigh 5.10g potassium hydrogen phthalate and 0.78g sodium hydroxide to prepare 1000mL of buffer solution with a pH of 5.56, weigh 0.5g of calcium carbonate samples before and after coating and dissolve them in 300mL of buffer solution, take samples once every 0.5h, take samples 6 times in succession, and use EDTA solution to titrate the Ca in the filtrate. 2+ , and we get Ca 2+ concentration, and plot Ca 2+ A graph showing concentration changes over time. Test results Fig. 9 shown.
[0112] Depend on Fig. 9 Ca 2+ The concentration-time curve shows that a layer of BaCO is coated on the surface of calcium carbonate. 3 After that, compared with blank calcium carbonate, the Ca 2+ The concentration changed from 23.5 mol / L to 23.4 mol / L, indicating that the coated BaCO 3 It does not improve the acid resistance of calcium carbonate; BaCO 3 The coating is converted into BaSO 4 After, Ca 2+ The concentration decreased significantly from 23.5 mol / L to 11.2 mol / L, indicating that the coated BaSO 4 It can significantly improve the acid resistance of calcium carbonate, probably due to the formation of BaSO 4 The coating layer is not very dense, resulting in that the calcium carbonate is not completely acid-resistant. In Comparative Example 3, the surface of the calcium carbonate is only partially coated with barium sulfate, resulting in its acid resistance being significantly worse than that of Example 1, and only slightly better than that of the blank sample.
[0113] From the above test results, it can be seen that the barium sulfate coated calcium carbonate core-shell structure product prepared by the method of the present invention has a regular morphology, good coating effect, and good acid resistance. This invention is expected to be applied in acid-resistant systems.
[0114] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a barium sulfate-coated calcium carbonate core-shell structure, characterized in that: The following steps are involved: (1) preparing calcium chloride and sodium carbonate solutions respectively, and then quickly mixing the two to prepare calcium carbonate, thereby obtaining a calcium carbonate suspension; (2) adding carbonate to the calcium carbonate suspension obtained in step (1), stirring to dissolve and fully mixing with the calcium carbonate, and then dropwise adding a mixed solution containing a calcium source and a barium source to react to obtain a CaCO3@BaCO3 slurry; (3) adding sulfuric acid dropwise to the CaCO3@BaCO3 slurry obtained in step (2) to obtain a CaCO3@BaSO4 slurry; (4) The CaCO3@BaSO4 slurry obtained in step (3) is filtered, washed and dried to obtain a CaCO3@BaSO4 composite powder, i.e., a core-shell structure of BaSO4 coated CaCO3.
2. The method for preparing a barium sulfate-coated calcium carbonate core-shell structure according to claim 1, characterized in that: In step (1), the concentrations of calcium chloride and sodium carbonate are both 0.1-1.0 mol / L.
3. The method for preparing a barium sulfate-coated calcium carbonate core-shell structure according to claim 1, characterized in that: In step (1), the particle size of calcium carbonate in the calcium carbonate suspension is 2-5 μm.
4. The method for preparing a barium sulfate-coated calcium carbonate core-shell structure according to claim 1, characterized in that: In step (2), the carbonate includes one or more of sodium carbonate, potassium carbonate, ammonium carbonate, and ammonium bicarbonate, and the amount added is calculated based on the amount that can just react completely with the calcium source and the barium source.
5. The method for preparing a barium sulfate-coated calcium carbonate core-shell structure according to claim 1, characterized in that: In step (2), the calcium source includes one or more of calcium chloride, calcium nitrate and calcium hydroxide, and the amount added is calculated as 0.4-1 times the amount of the barium source.
6. The method for preparing a barium sulfate-coated calcium carbonate core-shell structure according to claim 1, characterized in that: In step (2), the barium source includes one or more of barium chloride, barium nitrate, and barium hydroxide, and the amount added is calculated so that the weight of BaCO3 generated is 2%-10% of the weight of calcium carbonate.
7. The method for preparing a barium sulfate-coated calcium carbonate core-shell structure according to claim 1, characterized in that: In step (2), the concentration of the mixed solution of the calcium source and the barium source is 0.1-1.0 mol / L, and the dropping rate is 5-20 mL / min.
8. The method for preparing a barium sulfate-coated calcium carbonate core-shell structure according to claim 1, characterized in that: The reaction time in step (2) is 1-3 h, and the reaction time in step (3) is 1-2 h.
9. The method for preparing a barium sulfate-coated calcium carbonate core-shell structure according to claim 1, characterized in that: In step (3), the concentration of sulfuric acid is 0.1-1.0 mol / L, and the dropping rate is 2-10 mL / min.
10. The method for preparing a barium sulfate-coated calcium carbonate core-shell structure according to claim 1, characterized in that: In step (4), the drying method is: drying in a forced air drying oven at a temperature of 105-150° C. for 12-24 hours.